Trade, Specialization and Cycle Synchronization : Explaining Output Comovement between Latin America, China and India - Calderon, Cesar (World Bank, Washington, DC, 2021)
The main goal of the present paper is to explain whether trade and output specialization patterns may help explain the evolution of output co-movement of Latin American countries China and India. Using a sample of 147 countries over the period 1965-2004 we update and extend the results in Calderon, Chong and Stein (2006) to show that higher trade intensity (especially more extensive intra-industry trade links) and more symmetric structures of production (as well as of exports and imports) may lead to more synchronous cycles. For the Latin America and the Caribbean (LAC) region as a whole, the model predicts fairly well the changes in output comovement of LAC countries China and India (more than 50 percent). However, the performance of the model across countries shows a wide variation.